Exploring the experiences of individuals living with recurrent benign paroxysmal positional vertigo (BPPV) in the Western Cape, South Africa - Hofmeyr, Louis Murray (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2024.